A comparative genome‐wide analysis of the ABC transporter gene family among three Gossypium species. Issue 4 (11th June 2021) - Cui, Baolu; Li, Yan; Zhang, Yanjie
Abstract: ATP‐binding cassette (ABC) proteins are powerful transporters and are involved in countless cellular processes of plant development. In the present study, 315, 169, and 170 ABC genes were identified in Gossypium hirsutum, Gossypium raimondii, and Gossypium arboreum, respectively. The ABC genes were clustered into eight subfamilies based on their structural and phylogenetic features. The ABC members within the same subfamily showed similar protein structures and motif composition. Both tandem and segmental duplication events appear to have shaped the extensive expansion of the ABC transporter gene family, with purifying selection being the primary driving force for evolution. Expression profiles derived from transcriptome data exhibited distinct expression patterns of GhABC genes in various tissues and in response to different abiotic stresses. Additionally, analyses of the expression patterns of syntenic GhABC paralog pairs across 10 tissues and at ovule and fiber development stages revealed their functional conservation, subfunctionalization, neo‐functionalization, and pseudogenization during evolution. Finally, the analysis of co‐expressed subnetworks and tissue‐specific expression profiles suggested several ABC gene members might be involved in fiber development. This research provides a comprehensive overview of the ABC transporter gene family and forms the basis for further functional analysis in cotton. Core Ideas: Subfamily‐specific expansion occurred in Upland cotton GhABC genes. The expected expression patterns indicated most GhABCs functional conservation during evolution. The novel expression patterns pointed some GhABC genes toward neofunctionalization. The expression levels of seven genes are higher during fiber elongation.